Find the general solution to
y'' − y'− 2y = 2e3x
"\\text{The general solution to the given differential equation is }\\\\\ny = y_p(x) + y_c(x)\\\\\n\\text{where $y_p(x)$ represents particular solution and $y_c(x)$ represents the complimentary }\\\\\n\\text{solution.}\\\\\n\\text{The characteristic equation is given by }y^2-y-2\\\\\n\\text{Hence y = -1 and y = 2, therefore the complimentary solution is given by}\\\\\ny_c = C_1e^{-x}+C_2e^{2x}\\\\\ny_p(t) = Ae^{3x}, y'_p(t) = 3Ae^{3x}, y''_p(t) = 9Ae^{3x}\\\\\n\\text{Substituting the above into the given differential equation, we have}\\\\\n9Ae^{3x}-3Ae^{3x}-2Ae^{3x}=2Ae^{3x}\\\\\n\\implies A = \\frac{1}{2}\\\\\n\\therefore y_p(x)= \\frac{1}{2}e^{3x}\\\\\n\\implies y = C_1e^{-x}+C_2e^{2x}+\\frac{1}{2}e^{3x}"
Comments
Leave a comment